Hepatic toxicity assessment of cationic liposome exposure in healthy and chronic alcohol fed mice. Issue 11 (November 2017) - Kermanizadeh, Ali; Jacobsen, Nicklas R.; Roursgaard, Martin; Loft, Steffen; Møller, Peter
Abstract: The utilisation of nanoparticles as the means of targeted delivery of therapeutics and/or imaging agents could greatly enhance the specific transport of biologically active payloads to target tissues while avoiding or reducing undesired side-effects. To allow for this to become a reality, the question of potential toxicological effects needs to be addressed. In the present investigation, a cationic liposome with prospective for medical applications was constructed and thoroughly assessed for any material-induced hepatic adverse effects in vivo − in healthy and alcoholic hepatic disease models and in vitro − (HepG2 cells). The data demonstrated that intravenous injection of liposomes did not cause any significant in vivo hepatic toxicity (inflammation, alterations in blood parameters, anti-oxidant depletion, acute phase response and histopathology) at doses of 200 μg per mouse in either healthy or chronically alcohol fed mice. Additionally, the in vitro material-induced adverse effects (cytotoxicity, inflammation or albumin secretion) were all also minimal. The data from this study demonstrated that the intravenous injection of cationic liposomes does not cause hepatic toxicity. This investigation is important as it investigates the toxicity of a nano-sized material in a model of alcoholic hepatic disease in vitro and in vivo . This is an area of research in the field of nanotoxicology that is currently almost entirely overlooked.